Tax Counseling PP No. 23 of 2018 on UMKM Business Actors in Gunung Gangsir Village, Pasuruan Regency - Alif Faruqi Febri Yanto; Apriana Rahmawati (Institut Teknologi dan Bisnis Asia Malang, 2023)
The aim is for UMKM to understand their tax obligations, namely registering, recording, calculating, depositing and reporting (5M) taxes as well as taking advantage of tax incentives provided by the government for business actors affected by the after Covid-19 pandemic. The incentive given to UMKM players is by reducing the PPh (Final PPh) rate to 0.5% of total turnover, in accordance with Government Regulation (PP) No. 23 of 2018. The method used in this activity is to create a Community Service (PKM) activity by providing online counseling regarding taxation (online system) to UMKM actors in Gunung Gangsir Village, Pasuruan Regency which includes the functions and obligations of taxation as well as a question and answer session. The results of this community service activity increase insight in the field of accounting which focuses on making simple financial reports, and how UMKM calculate their taxes according to tax regulations. Lack of understanding about taxation makes many UMKM ask how to register, record, calculate, pay and report (5M) their taxes.